Nodal Injection of Agrobacterium tumefaciens for Gene Functional Analysis in Peanut: An Appraisal - Malizukiswe Vincent Vacu; Chunjiao Jiang; Haojie Sun; Guangdi Yuan; Jing Yu; Jun Zhang; Chuantang Wang (Agronomy)
Peanut is a key cash crop worldwide, yet the limited availability of functional genes and markers for breeding hinders further progress, largely due to the lack of an efficient and user-friendly transformation system. This study aimed to comprehensively evaluate the effectiveness of nodal agroinjection, a novel transformation technique we developed for peanut, by introducing the soybean cold-tolerance gene SCTF-1. Putative transgenic seeds and seedlings were screened using genomic DNA PCR, while transgene expression was analyzed via qRT-PCR and phenotypic assessments. Southern blotting confirmed the stable integration of SCTF-1. The transgenic seedlings displayed enhanced chilling tolerance, characterized by increased proline accumulation, reduced malondialdehyde (MDA), and elevated peroxidase (POD) activity. These findings demonstrate that nodal agroinjection is an efficient and reliable approach for generating transgenic peanut and analyzing gene function. This method offers a promising alternative to conventional tissue culture-based transformation strategies.